Crystal engineering principles: fluoroquinolone salts - Dandela, Rambabu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: ciprofloxacin; Fluoroquinolone; norfloxacin

Electron transfer rate analysis of a site-specifically wired copper oxidase - Schlesinger, Orr; Pasi, Mor; Dandela, Rambabu; Meijler, Michael M.; Alfonta, Lital (Physical Chemistry Chemical Physics, 2018)
Electron transfer kinetic parameters of site-specifically wired copper oxidase were investigated. The enzyme's orientation towards the electrode was controlled by incorporation of propargyl-L-lysine as a site-specific anchoring point. Herein, we demonstrate the importance of immobilization orientation and how it affects electron transfer efficiency and kinetics to each of the enzyme's two active sites.

Ligand/additive/base-free C(sp(2))-H activation and isocyanide insertion in PEG-400: synthesis of indolizine/imidazoline-fused heterocycles - Kumar, K. Shiva; Rajesham, Bandari; Kumar, N. Praveen; Ramulu, Meesa Siddi; Dandela, Rambabu (ChemistrySelect, 2018)
A ligand/base/metal oxidant free Pd-catalyzed C(sp(2))-H activation, followed by isocyanide insertion to synthesize indolizine/imidazoline fused heterocyclics in PEG-400 as a recyclable solvent. The present transformation is greener and an efficient strategy using oxygen as external oxidant. The spectroscopic properties of selected indolizine/imidazoline fused heterocyclics were studied by UV-visible and fluorescence spectroscopy.

Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Total synthesis of an anticancer natural product (+/-)-peharmaline A and its analogues - Kulkarni, Akshay S.; Shingare, Rahul D.; Dandela, Rambabu; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2018)
First total synthesis of a rare beta-carboline-vasicinone hybrid alkaloid (+/-)-peharmaline A has been accomplished in just 3 steps starting from known compounds. Stereoselective Pictet-Spengler reaction to nitrogenated tertiary carbon center and one-pot construction of the tricyclic skeleton of vasicinone are the highlights of present synthesis. We have also synthesized structurally close analogues of the natural product by following the developed route.

Neural anti-inflammatory natural product periconianone A: total synthesis and biological evaluation - Kalmode, Hanuman P.; Patil, Suhag S.; Handore, Kishor L.; Athawale, Paresh R.; Dandela, Rambabu; Verma, Abhishek Kumar; Basu, Anirban; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2019)
Total synthesis of periconianone A, an eremophilane-type sesquiterpenoid with impressive neural anti-inflammatory potential, has been accomplished. Diels-Alder/aldol strategy to construct tetrahydro-naphthalene-2,6-dione scaffold, allylic oxidation of dienone using DBU/O-2 and postulated biomimetic aldol reaction to construct 6/6/6 tricyclic system are the highlights of the present synthesis. Furthermore, the synthesized (+/-)-periconianone A and two close analogs were tested for their neural anti-inflammatory activity using various assays. In the course of our study we found a structurally simplified analog is superior to (+/-)-periconianone A.
Keywords: Aldol; Allylic oxidation; Biological evaluation; Cytotoxicity; Diels-Alder; Periconianone A

Naftopidil molecular salts with improved dissolution and permeation - Mannava, M. K. Chaitanya; Dandela, Rambabu; Tothadi, Srinu; Solomon, K. Anand; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Naftopidil (NFPD) is a alpha 1 adrenoceptor antagonist drug. Low solubility and low permeability are the major drawbacks of this drug. The synthesis of multicomponent crystalline forms of this amine functional group drug with carboxylic acid coformers, both achiral and chiral acids, provides a solution to improve its solubility as well as permeability. Nine molecular salts were crystallized by liquid-assisted grinding followed by isothermal crystallization. Single-crystal X-ray diffraction analysis of the molecular salts showed that the structures are stabilized by strong N-H center dot center dot center dot O and O-H center dot center dot center dot O and weak C-H center dot center dot center dot O hydrogen bonds in the solid state. The bulk phase purity of new solid forms was confirmed by powder X-ray diffraction (PXRD), and the crystalline products were further characterized by IR spectroscopy and thermal analytical techniques (differential scanning calorimetry). The molecular salts exhibit superior dissolution rates compared to pure NFPD. However, during dissolution, NFPD showed decrease in concentration after 60 min for all salts due to precipitation. The supersaturation occurred due to salt disproportionation, which generates insoluble NFPD, as confirmed by PXRD of the residue. The salts reach high saturation concentration before 60 min, which is indicative of immediate release formulation to achieve fast onset of therapeutic activity. Moreover, the salts exhibit high saturation in phosphate buffer saline media and improved permeability compared to the pure drug. Finally, the D,L-malic acid racemate of NFPD shows enhanced dissolution and permeability compared to all other salts and pure NFPD.

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Fluorobenzoic acid coformers to improve the solubility and permeability of the BCS class IV drug naftopidil - Mannava, M. K. Chaitanya; Bommaka, Manish K.; Dandela, Rambabu; Solomon, K. Anand; Nangia, Ashwini K. (Chemical Communications, 2022)
Crystalline salts of the low solubility and low permeability drug naftopidil were investigated with mono-, di-, tri-, and tetrafluorobenzoic acids as coformers to show that 245TFBA (2,4,5-trifluorobenzoic acid) is the optimal salt with faster dissolution and high permeability, thereby opening the study of fluorinated coformers in pharmaceutical cocrystals and salts.

Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.

Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates

Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.

New binary adducts of panobinostat with different carboxylic acid based NSAIDs: structural analysis and physicochemical properties investigation - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Shaikh, Tabrez R.; Jadab, Madhusmita; Pal, Satyanarayan; Dandela, Rambabu (ChemistrySelect, 2024)
Adoption of multitarget, cost-effective fixed-dose medication combinations can help lower the pill load without increasing the risk of adverse events. In this study, three new 1:1 drug-drug binary solid forms of panobinostat (PNB) and nonsteroidal anti-inflammatory drugs (NSAIDs) were effectively synthesized by liquid-assisted grinding and slow evaporation crystallization techniques. The obtained solid forms were extensively characterized by various analytical techniques. The structural investigation revealed that all molecular adducts formed salt with a comparable R42\${\textbackslashmathrm{R}}_4<\^>2\$(10) graph set pattern created by heteromeric interactions formed between PNB and corresponding salt formers. To determine the dissolving behavior of the newly developed adducts, solubility tests were performed at various pH levels (pH 1.2 and pH 7), and the results indicated that the solubility of all forms is increased at pH 7.0, particularly PNB.NIF has a solubility of 0.195 mg/mL, which is seven times higher than the parent drug. Furthermore, PXRD was used to assess the stability of the synthesized adduct at varied temperature and humidity levels and it was found that all the adducts are stable. Based on the findings, we hope that the newly found PNB drug-drug binary adducts have possible potential to broaden the use of drug combinations without changing the chemical structures.
Keywords: Drug-drug salts; Heteromeric interactions; Hydrogen bond; Non-steroidal anti-inflammatory drugs; Panobinostat

Novel molecular adducts of an anti-cancer drug vandetanib with enhanced solubility - Bandaru, Ravi Kumar; Giri, Lopamudra; Krishna, Gamidi Rama; Dandela, Rambabu (Crystengcomm, 2024)
The solubility, permeability, and dissolution rate of an active pharmaceutical ingredient (API) are critical factors in determining its pharmacokinetic performance in oral dosage forms. Modifying these properties can potentially enhance the drug's pharmacokinetics. Vandetanib (VDTB), classified as a class II anti-cancer drug in the biopharmaceutical classification system (BCS), suffers from low solubility (0.008 mg mL-1) and an extended pharmacokinetic half-life (19 days), necessitating the administration of high doses, which leads to undesirable side effects. To address this issue, we have employed a crystal engineering approach to enhance the solubility of VDTB. We employed the liquid-assisted grinding (LAG) method followed by the slow evaporation technique to prepare novel solid forms of VDTB by incorporating various aliphatic dicarboxylic acids, including succinic acid (SUA), adipic acid (ADA), pimelic acid (PIA), azelaic acid (AZA), and sebacic acid (SBA). These newly obtained solid forms were characterized by SC-XRD, PXRD, TGA, and DSC experiments. The crystal structure analyses revealed a proton transfer between the carboxylic acid group of aliphatic acids and the N-methyl piperidine moiety of VDTB, confirming salt/adduct formation. Additionally, all of the molecular salts were stabilized by charge-assisted N+-HMIDLINE HORIZONTAL ELLIPSISO- hydrogen bonds, while the parent VDTB crystal structure is stabilised by N-HMIDLINE HORIZONTAL ELLIPSISN interactions. Moreover, the solubility and dissolution rate of these new solid forms were assessed in a pH 7.4 phosphate buffer medium, with the results indicating that all of the solid forms, except for VDTB:SBA, exhibited higher solubility compared to pure VDTB. These findings offer promising prospects for the development of an improved VDTB formulation with enhanced pharmacokinetic properties. Successful attempt to improve the solubility and dissolution rate of Vandetanib - an anti-cancer drug, by crystal engineering approach.
Keywords: Amorfization; hydrate; Parameters; Salt; Thyroid-Cancer

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility